Editorial Management of Kanalindonesia.com Online News as Information Media - Fitriani, Nanda; Khadafi, Muhammad; A. Fikri Amiruddin Ihsani (Kediri Journal of Journalism and Digital Media (KJOURDIA), 2024)
Editorial management is the main key in managing online news content, especially in Kanalindonesia.com as a relevant and dynamic information media. This study aims to determine the editorial management strategies and practices applied by Kanalindonesia.com in presenting information effectively and up-to-date. The research method used is descriptive analysis with a qualitative approach. Data was collected through interviews, observations, and analysis of online news content published by Kanalindonesia.com. The results showed that the editorial management carries the approach of Planning, Organizing, Actuating, and Controlling. The process of collecting, editing, and disseminating news is carried out in a structured and efficient manner in accordance with journalistic principles. The selection of topics, the use of reliable sources of information, and the application of ethical journalism principles are the main focuses in presenting news. In addition, Kanalindonesia.com also implements controls on news content products that are carried out once a month. This is in order to form management that carries responsibility and can achieve the goals of the company.